The Armourer's Prentices - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Armourer's Prentices" by Charlotte M. Yonge is a historical novel written in the late 19th century. Set during the early Tudor period, the story revolves around two brothers, Ambrose and Stephen Birkenholt, who are forced to seek their fortunes in the world following their father's death. As they navigate the challenges of their new lives, they encounter various characters and situations that shape their journey and character development. The opening of the novel introduces readers to the idyllic setting of the New Forest, where the Birkenholt family lives in a picturesque lodge. Following the death of their father, tension arises between the brothers and their resentful elder brother, John, alongside their stepmother. Driven by a desire for independence and a longing for adventure, Ambrose and Stephen decide to leave their home, taking their beloved old dog, Spring, with them. The narrative begins to shape a journey filled with emotion, as Stephen grapples with the loss of his father and the impending separation from their familiar world. As they venture into the wider world, they are determined to seek out their uncle in London, whose connections they hope will help them find their place in society. (This is an automatically generated summary.)
Release date is 2006-02-01
David Price
Keywords: Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction